Prevention of neuronal apoptosis by astrocytes through thiol-mediated stress response modulation and accelerated recovery from proteotoxic stress. Issue 12 (December 2018) - Gutbier, Simon; Spreng, Anna-Sophie; Delp, Johannes; Schildknecht, Stefan; Karreman, Christiaan; Suciu, Ilinca; Brunner, Thomas; Groettrup, Marcus; Leist, Marcel
Abstract The development of drugs directly interfering with neurodegeneration has proven to be astonishingly difficult. Alternative therapeutic approaches could result from a better understanding of the supportive function of glial cells for stressed neurons. Therefore, here, we investigated the mechanisms involved in the endogenous neuro-defensive activity of astrocytes. A well-established model of postmitotic human dopaminergic neurons (LUHMES cells) was used in the absence ('LUHMES' mono-culture) or presence ('co-culture') of astrocytes. Inhibition of the LUHMES proteasome led to proteotoxic (protein aggregates; ATF-4 induction) and oxidative (GSH-depletion; NRF-2 induction) stress, followed by neuronal apoptosis. The presence of astrocytes attenuated the neuronal stress response, and drastically reduced neurodegeneration. A similar difference between LUHMES mono- and co-cultures was observed, when proteotoxic and oxidative stress was triggered indirectly by inhibitors of mitochondrial function (rotenone, MPP+ ). Human and murine astrocytes continuously released glutathione (GSH) into the medium, and transfer of glia-conditioned medium was sufficient to rescue LUHMES, unless it was depleted for GSH. Also, direct addition of GSH to LUHMES rescued the neurons from inhibition of the proteasome. Both astrocytes and GSH blunted the neuronal ATF-4 response and similarly upregulated NRF-1/NFE2L1, a transcription factor counter-regulating neuronal proteotoxic stress. Astrocyte co-culture also helped to recover the neurons' ability to degrade aggregated poly-ubiquitinated proteins. Overexpression of NRF-1 attenuated the toxicity of proteasome inhibition, while knockdown increased toxicity. Thus, astrocytic thiol supply increased neuronal resilience to various proteotoxic stressors by simultaneously attenuating cell death-related stress responses, and enhancing the recovery from proteotoxic stress through upregulation of NRF-1.